2017
DOI: 10.7197/cmj.v39i1.5000186627
|View full text |Cite
|
Sign up to set email alerts
|

Learning Needs of Adult Patients Surgery

Abstract: SUMMARYObjective: The purpose of the study was to identify the learning needs of adult surgical patients. Method: The study design used was cross-sectional and descriptive. Four hundred and twenty three adult surgical patients were included. Data, questionnaire and The Patient Learning Needs Scale-(PLNS), Turkish version, were used. The scores were then statistically analyzed using the mean, standard deviation, independent sample t test, ANOVA and Mann-Whitney U test. Results: The average age of patients was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
3
0
7
Order By: Relevance
“…The previous results were in the same line with Hansen and Sampognaro (Hansen and Sampognaro, 2019), in Malmo, who considered wound care, was the most signi icant self-perceived learning needs for patients after PCI. Also a study conducted in Turkey by Yilmaz (Yilmaz, 2017) showed that more than half of the patients did not receive discharge details after the operation. As well, a study carried out in Norway byValaker et al (Valaker et al, 2017) who assessed Continuity of care following percutaneous coronary intervention and reported that patients lacked knowledge about what to expect and how to access the health care system following discharge from hospital.…”
Section: Resultsmentioning
confidence: 99%
“…The previous results were in the same line with Hansen and Sampognaro (Hansen and Sampognaro, 2019), in Malmo, who considered wound care, was the most signi icant self-perceived learning needs for patients after PCI. Also a study conducted in Turkey by Yilmaz (Yilmaz, 2017) showed that more than half of the patients did not receive discharge details after the operation. As well, a study carried out in Norway byValaker et al (Valaker et al, 2017) who assessed Continuity of care following percutaneous coronary intervention and reported that patients lacked knowledge about what to expect and how to access the health care system following discharge from hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Araştırmaya katılan cerrahi hastalarının HÖ-GÖ'ye ait genel puan ortalamasının 199,38±39,35 olduğu saptandı. HÖGÖ alt gruplarında, önemlilik düzeyi bakımından hastaların en yüksek puanı tedavi ve komplikasyonlar (4,17) alt boyutundan aldığı, bunu sırasıyla ilaçlar (4,12) ve yaşam aktiviteleri (4,10) alt boyutlarının izlediği belirlendi. Araştırmaya katılan hastaların sürekli kaygı puan ortalamasının 41,59±8,51, durumluk kaygı puan ortalamasının 38,84±10,04 olduğu belirlendi (Tablo 2).…”
Section: Bulgularunclassified
“…HÖGÖ'nün kullanıldığı benzer çalışmalarda da genel cerrahi hastalarının öğrenim gereksinimlerinin yüksek olduğu belirlendi. 5,7,12,13,[15][16][17][18] Bu çalışmanın sonucu, daha önce yapılan çalışmalardan elde edilen sonuçlara benzerdir. Bu sonuçlar, genel cerrahi hastalarının öğrenim gereksinimlerinin yüksek olduğunu göstermektedir.…”
Section: Hastalarin öğReni̇m Gereksi̇ni̇mleri̇ne İli̇şki̇n Bulgulari...unclassified
“…Çalışmamızda HÖGÖ alt gruplarından en düşük puan ise duruma ilişkin duygulardan (6,58±1,67) elde edilmiştir. Literatürde çalışma sonucumuzu destekleyen çalışmalar mevcuttur 3,8,10,12,16,23 . Çalışmamızda hastalardaki bazı parametrelerin HÖGÖ alt boyut puanları üzerindeki gücüne bakıldığında sosyo-demografik özelliklerden cinsiyet ile yaşam aktiviteleri (p=0,027), yaşam kalitesi (p=0,004) ve cilt bakımı (p<0,001) alt grupları; yaş ve meslek ile sadece yaşam kalitesi alt grubu (sırasıyla p=0,008, p=0,029), ekonomik durum ile cilt bakımı (p=0,020) alt grubu arasında anlamlı fark saptanmıştır.…”
Section: Veri Toplanmasıunclassified